Salmonella enterica serovar Minnesota urosepsis in a patient with Crohn’s disease in the absence of recent or current gastrointestinal symptoms - Steinebrunner, Niels; Sandig, Catharina; Zimmermann, Stefan; Stremmel, Wolfgang; Eisenbach, Christoph; Mischnik, Alexander (The journal of medical microbiology, 2013)
Salmonella enterica serovar Minnesota is a rarely isolated organism in clinical samples mainly grown from stool cultures. Sepsis due to Salmonella is known in severely immunocompromised patients, but so far urosepsis due to S. enterica serovar Minnesota has not been described. We report a case of a 31-year-old patient suffering from Crohn’s disease treated with infliximab and azathioprine, in whom was implanted a double-J ureteric catheter for urolithiasis. The patient presented with urinary tract infection and severe sepsis. S. enterica serovar Minnesota was grown from urine and blood cultures. After empiric antimicrobial treatment with meropenem and vancomycin, treatment was changed to ceftriaxone. Antimicrobial treatment was continued for a total of 3 weeks without evidence of Salmonella recurrence on follow-up visits. Salmonella spp. rarely cause urinary tract infection and sepsis. However, in immunocompromised patients, non-typhoidal salmonellosis merits a thorough clinical and microbiological evaluation.,
First published: 01 September 2013
Gesehen am 15.02.2022